2021
DOI: 10.28934/jwee21.34.pp61-75
|View full text |Cite
|
Sign up to set email alerts
|

Online Social Networks and Women’s Entrepreneurship: A Comparative Study between Iran and Hungary

Parisa Bouzari,
Aidin Salamzadeh,
Maryam Soleimani
et al.

Abstract: The present study aimed to investigate the effect of online social networks on women’s entrepreneurship in Hungary and Iran in a comparative study. The statistical population of the present study consists of women entrepreneurs active in the field of online businesses in Iran and Hungary. The questionnaire was distributed via online links on social networks (on the online business website, Twitter, Facebook, and Instagram), and respondents were asked to answer questions if they were women entrepreneurs. ANOVA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…As advocated by the AFT, such skills will promote fairness and equal opportunities for African women in a variety of circumstances and regions. This is reinforced in the study by Bouzari et al (2021), which revealed that online social networks (Facebook and Instagram) significantly facilitate women's participation in entrepreneurship.…”
Section: Social Motivesmentioning
confidence: 83%
“…As advocated by the AFT, such skills will promote fairness and equal opportunities for African women in a variety of circumstances and regions. This is reinforced in the study by Bouzari et al (2021), which revealed that online social networks (Facebook and Instagram) significantly facilitate women's participation in entrepreneurship.…”
Section: Social Motivesmentioning
confidence: 83%
“…The mean COV in the first study was 0.18, which dropped to 0.16 in the second study, thus showing an acceptable consensus in this study (Wong et al, 2020). Inter‐class correlation (ICC) coefficient value was confirmed in consistency terms to ensure validity (Bouzari et al, 2021; Fekete‐Farkas et al, 2021; Khajeheian & Ebrahimi, 2021). Specialists requested to rate the questionnaire according to the “average measurement of each factor.” These scores were applied to evaluate the ICC coefficient.…”
Section: Methodsmentioning
confidence: 95%
“…Modifications in technology, and hence consumer habits, have increased online purchasing (Garcia et al 2020). In growing regions, social media marketing, startups, and various web tools are increasingly important (Bouzari et al 2021). In the midst of the new normal brought on by the coronavirus disease 2019 (COVID-19), mobile grocery shopping apps have become a lifeline for many consumers who have chosen to shop safer (Bruwer et al 2021).…”
Section: Grocery Shopping Mobile Appsmentioning
confidence: 99%